CLINICAL, SEROLOGICAL AND PATHOLOGICAL STUDY OF A NEWCASTLE VELOGENIC VIRUS STRAIN IN QUAILS (COTURNIX COTURNIX JAPONICA) - Quevedo C., Tatiana (2009)
The objective of the study was to determine the susceptibility, pathological effect, and serological response induced by a velogenic viscerotropic strain of Newcastle disease virus (vvNDV). For this purpose, 40 female quails (Coturnix coturnix japonica) were raised. Twenty were nasal and ocular inoculated with a vvNDV strain and 20 remained as a control group. Tissue samples and cloacae swaps of all birds were collected for histopathology analysis and virus isolation. Blood samples were collected during 5 weeks after the viral challenge to detect antibodies against NC virus using the hemaglutination inhibition (HI) test. In 40% of the inoculated birds was observed severe clinical signs and 20% mortality. The inoculated group registered an increase in the antibody level after day 7 post inoculation (MGT 6.1), reaching the highest level at 14 days post inoculation (MGT 29.9), whereas the control group did not register seroconversions. The viral isolation was obtained from cloacae swabs of the affected animals. The control group did not show signs of illness or histopathologycal changes.